The Portrayal of Amal's Diasporic Identity in Susan Abulhawa's Mornings in Jenin - Aimatul Ayu Maghfiroh (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2020)
This study analyzes the portrayal of diasporic identity in the protagonist character in Susan Abulhawa’s Mornings in Jenin. This novel has a post-colonial background as its central theme. Amal as the protagonist character, is moving to several countries, and she is expected to have a diasporic identity. To get the prospect data, this study is using the post-colonial approach and theory, diaspora, and diasporic identity theories. To analyze, this study uses a critical interpretation of data analysis. In conclusion, Amal's diasporic identity can be shown when she found the difference between her and American. She was an Arab who has different cultural values to American culture, and then she began to understand the differences. This study support William Safran’s the ideal types of diaspora because Amal shows the five out of six features.